2017
DOI: 10.1590/0103-1104201711315
|View full text |Cite
|
Sign up to set email alerts
|

Irregularidades sanitárias na promoção comercial em rótulos de produtos para lactentes e os riscos para a saúde

Abstract: RESUMORegulamentações sanitárias para crianças e lactentes buscam controlar estratégias mercadológicas que estimulam o consumo de certos produtos. Na investigação realizada em pontos de venda, verificou-se heterogeneidade na frequência de falhas na rotulagem de bicos, chupetas e mamadeiras em várias marcas. Deficiências nas informações sobre o controle de fabricação e os aspectos de proteção ao aleitamento natural indicam uma conduta intencional das marcas líderes para a manutenção dessa situação, que pode ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
(20 reference statements)
0
3
0
1
Order By: Relevance
“…18 In Piracicaba, in the state of São Paulo, two thirds of the drugstores and half of the supermarkets used special exposure as a marketing strategy, and as an auxiliary strategy they used special offers and gifts. 19 Our study found a greater number of promotions in the eastern and central regions of the city and in the main streets, which may be directly related to the greater movement of people, due to the high concentration of commercial establishments present there. In the eastern sector, the presence of attractive establishments stands out, such as shopping malls, the Municipal Administrative Center, the Federal University of Uberlândia, sports parks and stadiums and large companies that operate in the agri-food, telecommunications and entertainment sectors, in addition to the region's main public hospital, the Clinical Hospital of the Federal University of Uberlândia and the Cancer Hospital.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…18 In Piracicaba, in the state of São Paulo, two thirds of the drugstores and half of the supermarkets used special exposure as a marketing strategy, and as an auxiliary strategy they used special offers and gifts. 19 Our study found a greater number of promotions in the eastern and central regions of the city and in the main streets, which may be directly related to the greater movement of people, due to the high concentration of commercial establishments present there. In the eastern sector, the presence of attractive establishments stands out, such as shopping malls, the Municipal Administrative Center, the Federal University of Uberlândia, sports parks and stadiums and large companies that operate in the agri-food, telecommunications and entertainment sectors, in addition to the region's main public hospital, the Clinical Hospital of the Federal University of Uberlândia and the Cancer Hospital.…”
Section: Discussionmentioning
confidence: 50%
“… 18 In Piracicaba, in the state of São Paulo, two thirds of the drugstores and half of the supermarkets used special exposure as a marketing strategy, and as an auxiliary strategy they used special offers and gifts. 19 …”
Section: Discussionmentioning
confidence: 99%
“…Os conflitos de interesses (CoI) existentes na relação da indústria com profissionais, associações e organizações de saúde, entidades de classes profissionais e órgãos governamentais, também são entraves para o cumprimento da NBCAL no comércio, colocando em risco o bem-estar e saúde dos indivíduos, pois priorizam os interesses mercadológicos e comprometem a fiscalização devido a condescendência ocasionada pelo relacionamento estabelecido entre os agentes em questão (Rule & Shamoo, 1997;Freedhoff & Hébert, 2011;Brasil, 2015b;Lopes, 2017).…”
Section: Discussionunclassified
“…A study conducted in the municipality of Piracicaba (SP), in 2012, also observed that there were more discounts and special exposures of bottle nipples, baby bottles and pacifiers in pharmacies than in supermarkets 8 . Another study, conducted in the main supermarket chain of the municipality of Teresina (PI), in 2009, observed that half of the establishments presented infractions in the marketing of infant formulas, bottle nipples, baby bottles and pacifiers, especially through special exposure 9 .…”
Section: Discussionmentioning
confidence: 99%